Taking charge of change [videorecording] (Carlsbad, CA : CRM Learning, 2004)
[Teach employees the skills necessary to understand and support change initiatives with this revised and updated version of a long-time CRM favorite. In the video, stunning visuals feature a rookie skydiver making his first solo jump... a powerful metaphor for the leap we take into the unknown each time we experience a change in our own work lives. Participants learn strategies for moving through the three stages of change including: Differentiate between "change" and "transition" -- Discover the three stages of change (Endings, Neutral Zone, Beginnings) -- Identify which of the three stages of change is more difficult for them and why -- Learn the causes or conditions around a change that can influence one's needs through the transition that follows it -- Understand how and why each person in a workgroup may experience transition stages differently -- Recognize the role of communication (within teams, between teams, and between management levels) in the transition process. The vignettes provide a realistic look at the types of changes we experience in our work lives, and the steps we can take to help manage our response to those changes. Source : CRM Learning webpage : http://www.crmlearning.com/taking-charge-of-change]